Conservation of Hariana cattle through Gaushala - a refreshing experience - Ramesh Kumar; Satbir Singh; P.K. Malik; B. Prakash (Journal of Livestock Biodiversity, 2025)
Hariana breed of indigenous cattle is an acknowledged dual-purpose breed reared mainly for production of bullocks to be used for draught purpose and milk production for human consumption. Since extensive mechanization of agricultural operations in the breeding tract of the breed, it has lost its utility, as Murrah buffaloes are preferred for milk production. The breed is now restricted to few pockets and the extensive network of Gaushalas throughout the state of Hariana and adjoining parts of Punajb, Rajasthan and Uttar Pradesh. The gaushala at Jind, Haryana was adopted in 1994 by the Haryana Agricultural University for the improvement and conservation of this precious germplasm. In this study, an evaluation of growth, milk production and reproduction traits has been done to see the impact of improvement programme and its impact on the conservation of the breed. In general there has been a significant improvement in body weight at different ages, i.e. birth, 3-Months and 6 months. Significant improvement in the reproduction traits- age at first calving, service period and inter-calving period was found. Similarly, there was an appreciable improvement in the milk productivity traits like, lactation milk yield, peak yield and lactation length. The study, thus demonstrates that with the introduction of scientific breeding and management, the gaushala network of the state can be exploited as a source of conservation and improvement of Hariana cattle.